Gender-Specific Variations in BMI Status of Students' Social Networking Site Usage: A Comprehensive Statistical Analysis - Behera, Deepak Kumar; Gartia, Rajendra (PT. Riset Press International, 2023)
The present study investigates the association between gender and body mass index (BMI) status through a comprehensive statistical analysis. A diverse sample of participants was utilized to examine the prevalence and distribution of different BMI categories among males and females. Statistical techniques, including crosstabulation, chi-square tests, and correlation analysis, were employed to analyze the data and determine the significance of the relationship. The results of the analysis revealed distinct gender-specific variations in BMI status. Among females, the majority fell into the normal weight category (n=89, 49.0%), while males showed a higher prevalence of overweight (n=32, 21.5%). The crosstabulation table further demonstrated the distribution of participants across gender and BMI status categories, providing valuable insights into the prevalence of specific BMI statuses among males and females. The chi-square tests confirmed a significant association between gender and BMI status (p < 0.001), indicating that gender significantly influenced the likelihood of being in specific BMI categories. This finding emphasizes the importance of considering gender-specific factors in understanding and addressing BMI-related health disparities. The correlation analysis revealed a moderate positive association between gender and BMI status (r=0.205, p < 0.001), indicating that as gender changed from female to male, there was a tendency for BMI status to shift from lower categories to higher categories.